2012
DOI: 10.1063/1.3679566
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in coercivity of Pulsed Laser Deposition-fabricated Fe-Pt thick film magnets by reducing droplets

Abstract: A high-speed Pulsed Laser Deposition method with the deposition rate of several ten microns per hour followed by a post-annealing process enabled us to obtain isotropic Fe-Pt thick film magnets with the L1 0 order phase. In the study, we investigated the relationship between droplets and coercivity of the post-annealing films. It was found that the reduction in the numbers of droplets enabled us to increase the coercivity although the average deposition rate decreased from 40 to 15 lm per hour. In the samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…4, and would prevent a stable movement of particles emitted from the target to the substrate. In addition, it has been found that the compositions of droplets differ from that of non-droplet part of Sm-Fe [16] and Fe-Pt [17] films prepared by the PLD method. Therefore, the unstable movement of the particles is possibly responsible to the scattering of the film composition and magnetic properties.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…4, and would prevent a stable movement of particles emitted from the target to the substrate. In addition, it has been found that the compositions of droplets differ from that of non-droplet part of Sm-Fe [16] and Fe-Pt [17] films prepared by the PLD method. Therefore, the unstable movement of the particles is possibly responsible to the scattering of the film composition and magnetic properties.…”
Section: Discussionmentioning
confidence: 95%
“…During the ablation, the target was rotated at the speed of 3.3-13 rpm and a multi-layered film was deposited on a Ta substrate. The deposited films were [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] in thickness. The layer numbers synthesized in one hour are deduced from the above rotation speeds as 396 and 1560, respectively.…”
Section: Methodsmentioning
confidence: 99%